THE DETECTION OF BULLYING AND ITS SYMPTOMS AMONG SCHOOL-AGED CHILDREN - Amirbekov, М.М. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
In this article, the problem of bullying among school-aged children is examined. The article is dedicated to identifying bullying and its symptoms through questionnaires.
Keywords: adolescent; bullying; aim; identify; result